Training Utilizing Playstore Application for Improving Reading Skills in Pasirkiamis Village Pasirwangi Samarang Garut Regency - Deasy Aditya Damayanti; Zoni Sulaiman; Asep Nurjamin; Ari Kartini; Yati Afriyanti (Fakultas Kewirausahaan Universitas Garut, 2021)
Abstract The problem of media utilization is experienced by teachers in Pasirkiamis Kec. Pasirwangi Samarang Village, Garut Regency. The village is projected to be a training village because of the potential of human resources it has. These efforts are realized through the implementation of Community Service activities in related villages. The form of activity offered to the community is Training to Utilize Playstore Application for Improving Reading Teaching Skills. In general, this training aims to develop teacher media literacy competencies for the purposes of BDR activities by utilizing the Playstore application on their respective devices, building the independence of the target audience in utilizing media. Pasirwangi Samarang Garut Regency was able to utilize the Playstore application on their respective devices, building the independence of the target audience in utilizing the media, not only the Playstore application but also Google Classroom and Augmented Reality in PJJ or BDR activities during the pandemic, as well as the public perception of media literacy of teachers in Pasirkiamis Village, Pasirwangi Samarang District, Garut Regency by using a Media Literacy questionnaire based on individual competence framework is very high. Abstrak Permasalahan pemanfaatan media dialami oleh para guru di Desa Pasirkiamis Kec. Pasirwangi Samarang Kabupaten Garut. Desa tersebut diproyeksikan untuk dijadikan desa pelatihan karena potensi sumber daya manusia yang dimilikinya. Upaya tersebut direalisasikan melalui pelaksanaan kegiatan Pengabdian kepada Masyarakat di desa terkait. Bentuk kegiatan yang ditawarkan kepada masyarakat ialah Pelatihan Memanfaatkan Aplikasi Playstore untuk Peningkatan Kemampuan Mengajar Membaca. Hasil evaluasi mengarah pada beberapa simpulan di antaranya para guru di Desa Pasirkiamis Kec. Pasirwangi Samarang Kabupaten Garut mampu memanfaatkan aplikasi Playstore di gawainya masing-masing, membangun kemandirian khalayak sasaran dalam memanfaatkan media, tidak hanya aplikasi Playstore tetapi juga Google Classroom serta Augmented Reality dalam kegiatan PJJ atau BDR selama masa pandemi, serta persepsi khalayak mengenai literasi media para guru di Desa Pasirkiamis Kecamatan Pasirwangi Samarang Kabupaten Garut dengan menggunakan angket Literasi Media berbasis Individual Competence Framework sangat tinggi.